The Role of GenBank in Sustainable Utilization of Algal Genetic Resources - Mustansar Abbas; Shafqat Rasool; Mudassar Khan; Iftikhar Younis Mallhi; Rimsha Zainab; Iqra Naeem; Shah Mulk; Arsalan Abid; Saira Ghaffar; Fethi Ahmet Ozdemir; et al. (Dialogue Social Science Review (DSSR), 2025)
This study explores the application of GenBank, an extensive genetic sequence database, for preserving the genetic diversity of beneficial algae. By utilizing GenBank’s comprehensive molecular archive, researchers can track genetic variations and safeguard rare or endangered algal species. This approach not only enhances our understanding of algal biodiversity but also supports conservation initiatives and encourages sustainable applications in biotechnology, agriculture, and environmental management. Integrating genetic data into conservation strategies establishes a robust framework for protecting both the ecological and economic significance of beneficial algae. Key words: Beneficial effects of algae, blue green algae, prokaryotes, reproductive traits, Kingdom Protista,